THE USE OF MODELING METHOD TO IMPROVE THESTUDENTS’ PUBLIC SPEAKING SKILL IN THE ERA OFCOVID-19AT THE TENTHGRADE STUDENTS OF SMKN 2 BONE - Fahriadi Muhdar; Dian Riani Said; Sirwanti Sirwanti; Hamka Hamka; Marni Binti Mare (Bajang Institute, 2022)
The purpose of this research was to find out of the use modeling method to improve the students’ public speaking skill in the era of covid-19 at the tenthgrade students of SMKN 2 Bone. In this research, the research erused the design of Classroom Action Research. The subject of the research were students at thetenth grade of SMKN 2 Bone. The number of students in the class was 26 students which consist of 8 maleand 18 female.In public speaking the rewere 10 aspectsof assessment consisting of state thepurpose, organizes the content, support side as,in corporates stories and examples, summarizes thema in idea(s), demonstrate sawareness oflistener’sneeds, speaks clearly with appropriate vocabulary and information, uses tone, speed, and volume as tools, demonstrates complexity of thoughtand vocabulary, and appears comfortabl ewith audience. The result of this research showed that using modeling method in teaching public speaking can improve students’ public speaking ability. Analysisof the data showed there was a improvement in public speaking from cycle 1 tocycle 2, where cycle 1 only got a score 50,1 and got an increase in score in cycle 2by81,7.